Business Model Canvas in the entrepreneurs’ business model: a system approach - Macha-Huamán, Roberto; Zavala-Zavala, Oscar Marcel; Soto, Fabiola Cruz Navarro; Suárez, Julio Samuel Zárate; Castañeda, Doris Rosario Yaya; Lucar, Rudy Gonzalo Chura; Jibaja, Leonardo Castilla; Mejía, Percy Junior Castro; Montoya, Celfa Mónica Samaniego; Casco, Roque Juan Espinoza; Romero-Carazas, Rafael (EAI Endorsed Transactions on Scalable Information Systems, 2023)
Objective: To describe the association of the four main areas of the entrepreneurs’ business model with the Business Model Canvas from a systems approach. Methods: Quantitative approach, non-experimental design with descriptive and correlational scope; the sample consisted of 181 entrepreneurs; the instrument used was the questionnaire. Results: The chi-square test showed that there are dependency relationships between the four business areas and the Business Model Canvas (BMC); in addition, there is a positive and significant association between (1) customer interface and the BMC (0.609); (2) product and BMC (0.540); (3) infrastructure management and BMC (0.671) and (4) financial aspects and BMC (0.658). Therefore, the study showed that the four main areas of the entrepreneurs’ business model are significantly associated with the nine modules of the Business Model Canvas. Conclusion: Despite the positive and significant association of the areas with the BMC, micro and small business entrepreneurs should seek greater positioning in the market, strengthen their value proposition to be competitive in the market, greater resource planning and key partners, and finally, train and be part of financial inclusion and education.